Liberté de manifestation publique dans la ville de Kisangani : utopie ou réalité. - Salumu, Fiston WANDJA; Mokomboli, Patty LONGOLI; Singa, Nathan IUNGBI; Kikwata, Héritier AMOSI (IJRDO - Journal of Social Science and Humanities Research, 2018)
The Democratic Republic of the Congo is being a country that have been gone through a long period of the dictatorship, was obliged to adopt a so-called February 18, 2006 constitution as amended to date to become a true state of the rights. Where democracy reigns. Thus, the said constitution includes provisions that guarantee human rights in all its dimensions, as in the case of the law of public manifestation guaranteed by the above-mentioned Constitution, Article 26, and part 1 and 2 which provides that "freedom of demonstration is guaranteed. Any event on the public roads or in the open air requires the organizers to inform in writing the competent administrative authority ". On the other hand, there are in practice serious violations of this right orchestrated by law enforcement officials in accordance with orders received from the politico-administrative authorities of the City in Kisangani, in the sense of preventing the exercise of this right. despite the fact that it is guaranteed by the fundamental law of the country, which requires a sanction in the eyes of the law in order to recognize the imposition of the law at all.